2001
DOI: 10.1034/j.1398-9995.2001.00881.x
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to pets and atopy‐related diseases in the first 4 years of life

Abstract: The results indicate that early-life exposure to pets or lifestyle factors associated with exposure to pets reduce the risk of developing atopy-related diseases in early childhood. However, these findings might also be explained by selection for keeping pets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
134
2
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(147 citation statements)
references
References 26 publications
9
134
2
2
Order By: Relevance
“…We did not observe an association between pet exposures and childhood asthma, findings that are consistent with several birth cohort studies (Lau et al 2000;Nafstad et al 2001;Ronmark et al 2002). Although some studies have found positive associations (McConnell et al 2002;Zheng et al 2002), others have found pets to be protective (Hesselmar et al 1999;Remes et al 2001).…”
Section: Discussionsupporting
confidence: 78%
“…We did not observe an association between pet exposures and childhood asthma, findings that are consistent with several birth cohort studies (Lau et al 2000;Nafstad et al 2001;Ronmark et al 2002). Although some studies have found positive associations (McConnell et al 2002;Zheng et al 2002), others have found pets to be protective (Hesselmar et al 1999;Remes et al 2001).…”
Section: Discussionsupporting
confidence: 78%
“…Some studies have shown that there were no significant associations between pet-keeping and allergies in childhood [7][8][9] or a "protective" effect on early pet-keeping [4,[10][11][12][13][14][15][16]. But some other studies revealed that the "protective" effect might be confounded by parental avoidance behavior or selection of particular pet species [10,16,17]. Still other studies have had different findings and concluded that petkeeping in the home is a risk factor for allergies [2,3,[17][18][19][20][21][22].…”
mentioning
confidence: 91%
“…Although pet-keeping might increase sensitization, it could alleviate the degree of the symptoms-development [1] and prevent children from getting hay fever [6]. Some studies have shown that there were no significant associations between pet-keeping and allergies in childhood [7][8][9] or a "protective" effect on early pet-keeping [4,[10][11][12][13][14][15][16]. But some other studies revealed that the "protective" effect might be confounded by parental avoidance behavior or selection of particular pet species [10,16,17].…”
mentioning
confidence: 99%
“…Pet ownership has been a potential risk factor for asthma. However, considering that asthmatic families tended to avoid pet raising 15,16 and that our cross-sectional design did not allow for delineation of cause and outcome between pet raising and asthma, this question was not inquired about in this investigation. We decided not to include them as indoor factors or covariates because inclusion of these factors might have given significant associations, but they would have been difficult to interpret for causality.…”
Section: E392mentioning
confidence: 99%